Development of Integrated Science Student Worksheets (LKPD) Based on a Scientific Approach on Environmental Pollution Material at SMPN 6 Padang Class VII - Yernis Rosmaini Sidan; Monica Prima Sari (Universe, 2022)
ABSTRACTThis research is a development research that aims to develop a valid and practical student worksheet based on a scientific approach to environmental pollution material at SMPN 6 Padang. The type of research used is Research and Development (R&D) using the 4-D model. At the dissemination stage it was not carried out due to time and cost limitations. The instruments used in this study were validation questionnaire sheets, practicality questionnaires. The resulting LKPD was validated by 3 expert validators, namely Science Faculty of Mathematics and Natural Sciences UNP lecturers using an instrument in the form of a validity questionnaire. The practicality test was carried out by 3 science teachers at SMP N 6 Padang using an instrument in the form of a practicality questionnaire. From the research results obtained the following results: (1) Science-based LKPD Science-based on environmental pollution material at SMPN 6 Padang class VII developed valid, with a validity test value of 79.92. (2) LKPD IPA based on the scientific approach on environmental pollution material at SMPN 6 Padang class VII which was developed practically, with the practicality test value by the teacher in the very practical category with a value of 96.